(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This research assessed the impact of parental self-beliefs on the reading skills of the grade one learners of Lahug Elementary School, Cebu City Division, during the school year 2024-2025. Anchored in the understanding that parents are vital contributors to children’s literacy development, the research examined how specific parental beliefs—particularly teaching efficacy, positive affect, verbal participation, reading instruction, knowledge base, resources, and environmental input—correlate with children’s reading skills. Employing a descriptive-correlational research design, the study involved 120 parent-child dyads from this public elementary school. Data collection used a validated questionnaire based on Epstein’s framework to assess parental beliefs and a standardized reading assessment, the Comprehensive Rapid Literacy Assessment (CRLA), to evaluate student reading performance. Results indicated that, although parents generally expressed positive beliefs about their role in fostering reading development, these beliefs did not show a statistically significant relationship with their children’s actual reading proficiency. This disconnect highlights a gap between belief and practice in home-based literacy support. Consequently, the study recommends implementing targeted reading intervention programs, specifically by designing a proposed Reading Enhancement Plan that not only reinforces positive parental beliefs but also equips families with practical strategies to actively support their children’s reading development both at home and in school.